1981
DOI: 10.1182/blood.v58.4.856.856
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical demonstration of terminal deoxynucleotidyl transferase in leukemia

Abstract: White blood cells from 22 patients with leukemia and lymphoma were studied for the presence of terminal deoxynucleotidyl transferase with a peroxidase-antiperoxidase method. The enzyme was detected in leukemic cells of 5 patients with acute lymphoblastic leukemia and 1 patient with chronic myelogenous leukemia, whereas 16 patients with different forms of leukemia or lymphoma were negative for this enzyme. Comparative studies using a biochemical and an indirect immunofluorescence assay revealed complete concord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…A previous study [26] on a small number of patients indicated concordance between the biochemical. indirect immunofluorescent, and immunoperoxidase methods for TdT using a different commercial primary antibody.…”
Section: Discussionsupporting
confidence: 63%
“…A previous study [26] on a small number of patients indicated concordance between the biochemical. indirect immunofluorescent, and immunoperoxidase methods for TdT using a different commercial primary antibody.…”
Section: Discussionsupporting
confidence: 63%
“…The methods of cytochemical staining with peroxidase, a-naphthyl butyrate esterase, chloroacetate esterase, acid phosphatase, and toluidine blue were those previously reported [8, [19][20][21]. Immunoperoxidase staining for TdT was according to the method of Hecht et al [22]. Conventional immunologic techniques for surface immunoglobulin and E-rosette were performed as described elsewhere [ 13,231.…”
Section: Materials and Methods General Methodsmentioning
confidence: 99%